2000
DOI: 10.1002/1096-911x(20001201)35:6<597::aid-mpo23>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic-acid-resistant neuroblastoma cell lines show alteredMYC regulation and high sensitivity to fenretinide

Abstract: Thus, RA-resistant NB cell lines can be sensitive (and in some cases collaterally hypersensitive) to 4-HPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 16 publications
1
61
1
1
Order By: Relevance
“…Unlike retinoic acid, fenretinide is able to induce apoptosis in a range of neuroblastoma cell lines, including some which are resistant to retinoic acid. 4 This makes fenretinide a potentially powerful agent for the treatment of neuroblastoma.…”
mentioning
confidence: 99%
“…Unlike retinoic acid, fenretinide is able to induce apoptosis in a range of neuroblastoma cell lines, including some which are resistant to retinoic acid. 4 This makes fenretinide a potentially powerful agent for the treatment of neuroblastoma.…”
mentioning
confidence: 99%
“…Treatment with 13cisRA for high-risk neuroblastoma takes place after high dose myeloablative therapy and radiotherapy but the most appropriate way to utilise fenretinide remains unclear. In vitro data showing that neuroblastoma cells selected for 13cisRA resistance are sensitive to fenretinide suggest that fenretinide may be useful for MRD remaining after 13cisRA treatment (5). However, the mechanisms of action of 13cisRA in vivo are unknown and in vitro selection may not be an appropriate model of treatment failure since it has not been demonstrated that patients who relapse after retinoid therapy do so because of inherent retinoid resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, prolonged disease stabilisation was induced in some neuroblastoma patients participating in a phase I trial when treated during partial remission (3). These encouraging clinical data, together with the observation that neuroblastoma cells shown to be resistant to 13cisRA are sensitive to fenretinide (5), have led to the incorporation of fenretinide in the treatment of MRD in a phase II trial. However, it is known that retinoic acid (RA) treatment can increase resistance to apoptotic agents (6)(7)(8), and whilst combining fenretinide with 13cisRA represents a promising clinical approach, there are important questions over the potential for interactions between these drugs which have yet to be addressed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations